Investigation of various algorithms on multichannel audio compression - Gunawan, Teddy Surya; Abdul Rashid, Siti Aisyah; Kartiwi, Mira (2017)
Multichannel audio or surround sound compression is rather more challenging to compress compare to mono and stereo audio. Nowadays, many methods and algorithms have been proposed to improve the compression performance on multichannel audio. This book focuses on performance evaluation of various algorithms on multichannel audio compression. First, we identified and investigated current state-of-the-art audio compression algorithms, both lossless and lossy compression, which can handle mono, stereo, 5.1, and 7.1 multichannel audio. Out of various algorithms available, AC3, AAC, and Ogg have been selected as lossy compression algorithms, while FLAC and MPEG-4 ALS have been chosen as lossless compression algorithms. Two performance measure were used in the experiments, i.e. compression ratio and encoding time. The results showed that among three lossy audio compression algorithms, AC3 has the fastest encoding time while Ogg Vorbis has the highest compression ratio. Furthermore, between FLAC and MPEG-4 ALS, FLAC has faster encoding time and MPEG-4 ALS has higher compression ratio. Overall, in terms of encoding time and compression ratio, it has been found that FLAC is the fastest coder while Ogg Vorbis has the highest compression ratio among five encoders evaluated.